Optimization of Natural Resources to Realize Community Welfare - Siti Ainul Kholipah; Muhamad Zaenal Asikin; Mijoyo Mijoyo; Iin Tarsini; Muhamad Khoerudin (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this study is to empower the people of Panambangan Village in realizing independence and welfare based on optimizing community potential, focusing on understanding the history of Panambangan Village, the origin of the name of the village, and the potential of its natural resources. The method used in this study is qualitative research method. The potential of Panambangan Village tourist attraction has a tourist attraction that until now has not been developed. Research results The wealth of tourism potential of Panambangan Village needs to be developed in order to support sustainable tourism. Recommendations that can be given to develop tourism potential are directed based on the condition of Panambangan Village whose status as a tourist village, but conditions on the ground have not reflected this. This is shown by the development of tourism which is still constrained by development costs. Even though Panambangan Village has many natural features and cultural traditions that can be considered quite exciting tourist attractions, The conclusion of this study shows that efforts to optimize natural resources can be vital in achieving community welfare by combining ecological sustainability and economic development.